English for Exam or Exchange? Tourism Scholars’ Perception of Business Communication Course - Joshi, Bishow Raj (ILAM इलम, 2023)
This paper attempts to investigate gaps between the course and real-field needs of communication skills in English in the tourism industry. Tourism scholars’ narrated learning experiences and the application of those learning experiences in the workplace were the research data. The analysis of the data results that the present Business Communication course has a positive role in introducing the international-level content needed in the tourism and hospitality industry. The prescribed books and reference materials are of international standard. However, due to the lack of effective pedagogical activities, no provision of practical examination, and lack of link of communication skills to other components of the program, this course has been taken as a general English course by the tourism scholars as though it claims to be English for tourism and hospitality. Therefore, this course needs in-depth scrutiny and revision to address the demand of tourism and hospitality entrepreneurs.